Identification of Campylobacter jejuni from Chicken Carcasses and Characterization of Their Antibiotic Resistance Using Molecular Approach - Susanty, S.; Dewanti-Hariyadi, R.; Kusumaningrum, H. D. (Tropical Animal Science Journal, 2025)
Campylobacter species, particularly Campylobacter jejuni and Campylobacter coli, are foodborne pathogenic bacteria that cause campylobacteriosis, an acute gastroenteritis in humans. The most important transmission source to humans is contaminated animal products, such as chicken carcasses. Recently, there has been a growing concern about emerging antibiotic-resistant pathogens, including Campylobacter. Improper use of antibiotics in livestock can increase the risk of antibiotic resistance and the transmission of resistant bacterial strains to humans. This study aims to identify the species of Campylobacter spp. isolated from chicken carcasses and detected their antibiotic resistance genes using MinION sequencing in C. jejuni isolates. The disc diffusion method was also used to evaluate their resistance to macrolide, tetracycline, and fluoroquinolone antibiotics. The study results show that C. jejuni was identified in 64% of the 25 isolates, while C. coli was identified in 36% of the isolates. Molecular testing on C. jejuni isolates revealed that macrolide resistance genes were absent, specifically the 23S rRNA and the ermB genes. The tetO gene encoding for tetracycline resistance was detected in 62.5% of the isolates, and all 16 isolates (100%) were found to have the gyrA gene. In C. jejuni isolates, the cmeABC gene, which functions as a multidrug efflux pump, was also detected. The antibiotic resistance of C. jejuni isolates based on the disc diffusion method indicated high resistance to fluoroquinolone antibiotics, followed by tetracycline antibiotics.